A revision of the genus Anepholcia Prout, 1924 with description of three new species from South East Asia (Lepidoptera, Noctuidae). Revision of Pantheinae, Contribution IV - Behounek, Gottfried; Kononenko, Vladimir (Zootaxa, 2011)
The genus Anepholcia Prout, 1924 of the subfamily Pantheinae is revised. Three new species (Anepholcia kobesi sp. n., A. brechlini sp. n. and A. philippina sp. n) from Sumatra and Phlippines are described. The misidentification of A. talboti Prout, 1924 by Kobes is corrected. A key for identification of Anepholcia species based on external characters and male genitalia characters is provided.